Single Ascending Dose Study to Assess Pharmacokinetic Linearity, Safety, and Tolerability of Trimetazidine - Modified Release in Healthy Human Subjects - Körnicke, Thomas; Arora, Deepa; Samad, Abdus; Kaplan, Sigal; Domahidy, Mónika; de Voogd, Hanka; Böhmert, Stella; Ramos, Rita Silveira; Jain, Shashank (Drug Research, 2020)
Aim This study assessed the linearity of pharmacokinetics (PK) of trimetazidine (TMZ) modified-release tablets (indicated in adults as an add-on therapy for stable angina pectoris) and measured its renal elimination, safety, and tolerability in healthy subjects.Methods This was a randomized, open-label, single-ascending dose study in healthy subjects. Subjects were administered with a single dose of 35, 70, or 105 mg TMZ-modified release tablets (six subjects each). Pharmacokinetic evaluations and safety analysis were performed before the first dose and till 48 h post-first dose.Results Following administration of 35, 70, and 105 mg TMZ-modified release; the Cmax (mean±SD) was 79.32 (±23.08), 153.17 (±23.08), and 199.67 (±23.08) ng/mL, the Tmax was 5.42 (±0.49), 4.51 (±1.27), and 4.57 (±0.96) h, t1/2 was 7.75 (±1.62), 6.40 (±1.23), and 6.50 (±1.18) h, AUC(0-inf) was 1116.89 (±378.35), 1838.39 (±284.50), and 2504.84 (±348.35) ng.h/mL, CLR was 13.70 (±2.24), 14.80 (±5.91), and 19.58 (±6.24) L·h−1 and CL/F was 33.69 (±8.51), 38.85 (±6.15), and 42.74 (±7.10) L·h−1, respectively. Slope estimates for AUC(0-inf), AUC(0-t), and Cmax were less than 1. Corresponding 95% CI of the slope for the AUC parameters excluded 1, indicating that the deviation from dose-proportionality was statistically significant. Corresponding 95% CI of the slope for Cmax included 1, indicating that the less than dose-proportional increase in Cmax was not statistically significant. No significant adverse events were observed.Conclusion Substantial deviation from a dose-proportional increase in AUC(0-inf) and AUC(0-t) suggested a non-linear PK for TMZ-modified release. Single dose of TMZ-modified release was well tolerated and safe.
Keywords: pharmacokinetics; drug delivery; drug research; clinical trials; cardiovascular pharmacology